THE IMPACT OF THE RUBBER DAM ON TAJ MAHAL - Kumar, Hemant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The planned rubber dam on the Yamuna, sited just 1.5 kilometres east of the Taj Mahal, intends to rehabilitate the river’s visual appeal, making boat excursions feasible again and softening water-related pollution around the World Heritage Site. This review investigates the dam’s prospective influence on tourism by sifting through e-sources—academic studies, chronicle archives, and X network forums. Evidence indicates the structure may elongate average length of stay, elevate earnings, and deepen visitor satisfaction by again showcasing the Taj’s reflection, soothing airborne dust, and removing complaints of the barren, malodorous extremities of the once-flowing river. The dam will put forward that which which sees increase in visitor stay, revenue, and experience via revival of scenic views and reduction in dust related pollution which in turn will in large part be a response to tourist complaints of the dry smelly riverbed. But at the same time there are issues of construction disruption, of pollution which will come to head, and of unconfirmed foundation issues which will in all probability put off visitors and damage Agra’s tourism image. We recommend in this regard that which of very thorough hydrogeological studies, pollution control, and stakeholder engagement to which we must see the growth of sustainable tourism which at the same time will preserve the Taj Mahal’s cultural integrity.